POSSESIVE CHARACTERIZATION OF NOAH CHARACTER IN MOVIE THE BOY NEXT DOOR DIRECTED BY ROB COHEN - Mohammad Zamroni; Khotimatul Husniah (JURNAL LITERASI, 2022)
This thesis focused on the tittle of the subject “Possesive Characterization Of Noah Character in The Boy Next Door Movie Directed By Rob Cohen. The objective problems in this thesis to know The possesive characterization of Noah character. To analyze this thesis the writer use steps of literature. In a literary work, like a movie there is a character.Character can be tangiblehuman, animals or other creature that has characteristic like humans. These are the characters that will have the greatest effect on the plot or are the most affected by what happens in the story. The qualitative descriptive is used to apply the data collection method and the data get from some steps, they are watching, comprehends the movie, choose and take the data that have related to the topic, selecting the important dialogues and making quotatios of the text to support this thesis. The methods of the study are qualitative methods that presented on descriptive ways that present all data and descriptive all intriks that has own meaning of analyze aspects. By this methods the researcher use a study approach on Noah character.The data primer of the researcher taking from the movie it self and also from the literatures that borrowed from the Panca Marga University libraries. This thesis analyze about The Boy Next Door. This movie tells someone which have a possesive personality, especially on the main character (Noah).After one-night standwith Claire and Claire end the relationship Noah began to showing his personality that very possesive and dangerous, his anger at Claire, teror, and hurting the people closest to Claire, her husband, her soon and her friend. So the researcher can analyze the story, and conclude that Noah character in this movie have a possesive personality